Brecha de género y etnia en enfermedad carotídea: experiencia de un hospital nacional peruano - Vetanzo-Sánchez, Georgette (2025)
Atherosclerotic carotid artery disease is a significant cause of cerebrovascular events worldwide. Current international guidelines for the management of this condition provide general recommendations that often overlook differences among specific population groups. Although sex- and race-related disparities in disease prevalence are acknowledged, there remains a notable lack of studies focused on the prevalence, progression, and management of carotid artery disease in Latina women.